COMMISSION 36: THEORY OF STELLAR ATMOSPHERES - Landstreet, John D.; Asplund, Martin; Spite, Monique; Balachandran, Suchitra B.; Berdyugina, Svetlana V.; Hauschildt, Peter H.; Ludwig, Hans G.; Mashonkina, Lyudmila I.; Nagendra, K. N.; Puls, Joachim; Randich, M. Sofia; Tautvaisiene, Grazina (Proceedings of the International Astronomical Union, 2008)
Commission 36 covers the whole field of the physics of stellar atmospheres. The scientific activity in this large subject has been very intense during the last triennium and led to the publication of a large number of papers, which makes a complete report quite impractical. We have therefore decided to keep the format of the preceding report: first a list of areas of current research, then Web links for obtaining further information.